2022
DOI: 10.3390/polym14071345
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Mechanical Properties of Self-Repairing Pectin Biopolymers

Abstract: Pectin’s unique physicochemical properties have been linked to a variety of reparative and regenerative processes in nature. To investigate the effect of water on pectin repair, we used a 5 mm stainless-steel uniaxial load to fracture glass phase pectin films. The fractured gel phase films were placed on a 1.5–1.8 mm thick layer of water and incubated for 8 h at room temperature and ambient humidity. There was no immersion or agitation. The repaired pectin film was subsequently assessed for its optical and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The low-profile pectin film was previously shown to be translucent, flexible, fracture resistant, and bioabsorbable. 10 , 15 , 23 , 28 , 29 Here, we showed that the pectin film was also rapidly and strongly adherent to the corneal surface―effectively sealing corneal incisions. The strongly adherent pectin was also used for en face harvest of the corneal epithelium.…”
Section: Discussionmentioning
confidence: 74%
“…The low-profile pectin film was previously shown to be translucent, flexible, fracture resistant, and bioabsorbable. 10 , 15 , 23 , 28 , 29 Here, we showed that the pectin film was also rapidly and strongly adherent to the corneal surface―effectively sealing corneal incisions. The strongly adherent pectin was also used for en face harvest of the corneal epithelium.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, our studies highlight the multi-functional potential of the pectin biopolymer. In previous work, we have shown that pectin films strongly bind to the surface glycocalyx of visceral organs with a mechanism of branched chain entanglement [ 14 , 41 , 42 ]. The strong adhesivity has led to a proposed function of pectin films as a sealant for visceral organ injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Pectin is among the most complex polysaccharides [64], being known for its unique chemical and functional characteristics [65]. It comprises approximately one-third of the dry substance in the cell walls of higher plants [66], particularly around actively dividing cells, soft plant tissues, cell corners, and middle lamella [64], and is responsible for intercellular adhesion and contributing to the overall plant structure and firmness [67].…”
Section: Pectin-based Vmasmentioning
confidence: 99%